Restaurant employees' perceptions of barriers to three food safety practices - Howells, Amber D.; Roberts, Kevin R.; Shanklin, Carol W.; Pilling, Valerie K.; Brannon, Laura A.; Barrett, Betsy B. (My University, 2008)
Limited research has been conducted to assess employees' perceptions of barriers to implementing food safety practices. Focus groups were conducted with two groups of restaurant employees to identify perceived barriers to implementing three food safety practices: handwashing, using thermometers, and cleaning work surfaces. Ten focus groups were conducted with 34 employees who did not receive training (Group A). Twenty focus groups were conducted with 125 employees after they had participated in a formal ServSafe training program (Group B). The following barriers were identified in at least one focus group in both Group A and Group B for all three practices: time constraints, inconvenience, inadequate training, and inadequate resources. In Group A, additional barriers identified most often were a lack of space and other tasks competing with cleaning work surfaces; inconvenient location of sinks and dry skin from handwashing; and lack of working thermometers and thermometers in inconvenient locations. Additional barriers identified most often by Group B were no incentive to do it and the manager not monitoring if employees cleaned work surfaces; inconvenient location of sinks and dry skin from handwashing; and lack of working thermometers and manager not monitoring the use of thermometers. Results will be used to develop and implement interventions to overcome perceived barriers that training appears not to address. Knowledge of perceived barriers among employees can assist dietetic professionals in facilitating employees in overcoming these barriers and ultimately improve compliance with food safety practices.
Keywords: Food safety; Focus groups; Perceived barriers; Handwashing; Thermometers; Cleaning work surfaces